NUTRI-SCORE SEBAGAI STRATEGI MANAJEMEN RISIKO KONSUMEN TERHADAP MAKANAN TIDAK SEHAT: TINJAUAN LITERATUR SISTEMATIS KEBIJAKAN PELABELAN NUTRISI - Yullyana, Ellena Manaby; Milad, Mohammad Khusnu (Jurnal Manajemen, 2025)
Basic human needs encompass not only food, clothing, and shelter, but also a sense of safety and control over health-related risks. In today’s fast-paced lifestyle, the consumption of packaged and convenience foods has risen significantly, prompting rapid growth in the processed food industry and increased market competition. This shift poses new challenges in managing dietary risks, particularly regarding the intake of unhealthy food that contributes to non-communicable diseases (NCDs) such as diabetes, whose prevalence continues to rise in Indonesia. This study employs a Systematic Literature Review (SLR) approach to evaluate the role of front-of-pack nutrition labeling—specifically formats such as Nutri-Score and Health Star Rating—as tools of consumer risk management. The findings indicate that clear and easily interpretable labeling designs are effective in improving nutritional literacy, influencing consumer behavior, and guiding healthier food choices. Thus, nutrition labeling acts not only as an information tool but also as a preventive risk mitigation strategy in public health. This review contributes to the discourse on labeling policy development and supports its integration into broader health risk management frameworks to promote healthier dietary practices.